Improving the OSH Knowledge of Indonesian Forestry Workers by Using Safety Game Application: Tree Felling Supervisors and Operators - Yovi, Efi Yuliati; Yamada, Yozo; Zaini, Mohammad Faiz; Kusumadewi, Chika Annisa Yonanda; Marisiana, Lerfi (Jurnal Manajemen Hutan Tropika, 2016)
This research focused on the possibility to improve the possession of OSH knowledge of Indonesian forestry workers, especially of both supervisor and operators who carried heavy responsibilities as executors of any forestry program. To meet the demand of both respondent groups, a prototype of a board - education game developed in 2015 called "The Felling Safety Games: Supervisor" was up-graded and modified. Data derived from questionnaires, direct observation, in-depth interviews, and logical assumption, provided information on (1) the recent perception of OSH knowledge, (2) the success of the education game implementation, and (3) factors that led to the success of the implementation. The fact that all respondents in this research were overrated on their OSH knowledge reflected serious problems in the field of OSH in the forestry work in Indonesia. It was satisfying to know that the safety game showed a very optimistic result, as the OSH knowledge of the workers were significantly improved after only 2-6 game repetitions. Another factor that led to the success of the implementation of the game was the performance of OSH agent who played a role as facilitator during the game. However, a strong management commitment developed based on a local-based OSH management system, remained as an important requirement for the creation of a safe work behaviour change and healthy workplace.